Pengaruh Senam Aerobik Low Impact Terhadap Kadar Gula Darah Lansia Prediabetes Di Panti Sosial Lanjut Usia (PSLU) Mandalika - Junendri Ardian; Solehah, Novia Zuriatun; Isasih, Widani Darma; M. Thonthowi Jauhari; Rizqika Mahardika (ARTERI : Jurnal Ilmu Kesehatan, 2024)
Low Impact Aerobics is a form of physical exercise that can increase strength, flexibility and muscle growth in a simple, cost-effective, fun and safe way. Previous research also shows that aerobic exercise has a significant impact on reducing blood glucose levels. This study aims to examine the impact of Low Impact Aerobic exercise on blood glucose levels in a group of elderly people who have prediabetes and are over 60 years old at the Mandalika Social Home for the Elderly (PSLU). This research uses quantitative methods with a One-Group quasi-experimental design. Pretest-Posttest Design to evaluate the effect of Low Impact Aerobic exercise on blood glucose levels in the elderly population suffering from prediabetes and aged over 60 years at the Mandalika Social Home for the Elderly (PSLU). The sampling method in this study used a purposive sampling method and data collection used sinocare to measure blood glucose levels before and after the intervention was given. The results of data analysis using the Paired T-Test showed a p value = 0.001, which shows that there is a significant difference in blood glucose levels before and after implementing Low Impact Aerobic exercise. Based on these findings, it can be concluded that Low Impact Aerobic exercise has a positive impact in reducing blood glucose levels from 160.30 mg/dl to 132.80 mg/dl in elderly people with prediabetes at the Mandalika Social Home for the Elderly (PSLU).